2007
DOI: 10.1007/s00227-006-0564-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and salinity on the trace element incorporation into statoliths of the common cuttlefish (Sepia officinalis)

Abstract: The use of statolith chemistry to trace migration pathways and distinguish populations of cephalopods is based on the assumption that the elemental composition of statoliths is influenced by physicochemical properties of the ambient environment. However, such influences have not been investigated experimentally up until now. This study presents the first microchemical analyses of cephalopod statoliths obtained from laboratory experiments under different controlled temperature and salinity conditions. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 52 publications
9
28
2
Order By: Relevance
“…Using these discriminant functions, only 22% of the recruits were correctly reclassified, which, with few exceptions, lie at the borders of the discriminant function analysis space generated by larvae ratios in the natal core of recruit statoliths collected from the northern region may be interpreted in relation to the presence of a persistent upwelling shadow inside Antofagasta Bay , Lagos et al 2008). This agrees with the significant reduction in Ba/Ca from southern to northern recruit statoliths, and might be associated with the negative effect of temperature in the incorporation of Ba as has been reported in studies conducted in gastropods (Zacherl et al 2003a, Zumholz et al 2007, Lloyd et al 2008 and bivalves (Carson 2010). Interestingly, pre-hatch larval statoliths (where individuals are fixed in place) do not show this pattern, and instead show a significant increase of the Ba/Ca ratio from southern to northern populations.…”
Section: Discussionsupporting
confidence: 89%
“…Using these discriminant functions, only 22% of the recruits were correctly reclassified, which, with few exceptions, lie at the borders of the discriminant function analysis space generated by larvae ratios in the natal core of recruit statoliths collected from the northern region may be interpreted in relation to the presence of a persistent upwelling shadow inside Antofagasta Bay , Lagos et al 2008). This agrees with the significant reduction in Ba/Ca from southern to northern recruit statoliths, and might be associated with the negative effect of temperature in the incorporation of Ba as has been reported in studies conducted in gastropods (Zacherl et al 2003a, Zumholz et al 2007, Lloyd et al 2008 and bivalves (Carson 2010). Interestingly, pre-hatch larval statoliths (where individuals are fixed in place) do not show this pattern, and instead show a significant increase of the Ba/Ca ratio from southern to northern populations.…”
Section: Discussionsupporting
confidence: 89%
“…We found evidence for a negative correlation between temperature and Ba uptake in both larval and juvenile shells, which is consistent with results of Zacherl et al (2003b) and Zumholz et al (2007), who both found a negative correlation in the aragonite structures of laboratory-reared molluscans. We found no significant relationship between DBa and salinity, which is also consistent with results from Zumholz et al (2007).…”
Section: Barium and Lead Uptakesupporting
confidence: 91%
“…We found no significant relationship between DBa and salinity, which is also consistent with results from Zumholz et al (2007). Ba is likely to be a useful addition to elemental tagging studies, even in situations where its concentration does not vary spatially, as uptake into molluscan shell appears to have a consistent relationship with temperature.…”
Section: Barium and Lead Uptakesupporting
confidence: 88%
See 2 more Smart Citations